Gerakan Filantropi Islam di Amerika - Fuad (Jurnal Studi Al-Qur’an, 2018)
Abstract This research aims to explore the development of Islamic Philanthropy movement in America covering the discussion on the institutional basis of Islamic Philanthropy, and its contributions toward the solidarity and the empowerment of muslim community. The research is a kind of literary research with the qualitative research method and multidisciplinary approach. The result shows that there are four institutional basis of Islamic Philantrophy in America; those are mosques, educational institutions, ethnic, and religious school of thought. The facts are also found that there is significant correlation between the existence of Islamic Philanthropy institution and government political policies on radicalism issues that adhered to muslim community in America.